2017
DOI: 10.14204/ejrep.30.13030
|View full text |Cite
|
Sign up to set email alerts
|

Personalidad, Procrastinación y Conducta Deshonesta en Alumnado de distintos Grados Universitarios

Abstract: Introducción. La personalidad, la procrastinación y la conducta deshonesta en el aula (o cheating) son variables que han demostrado tener una influencia importante en el aprendizaje. Con todo, pocas veces se han estudiado todas juntas y menos teniendo también en cuenta el género del alumno y su elección de la carrera. Este trabajo analiza todas estas variables en estudiantes de distintas facultades de la Universitat Autònoma de Barcelona, UAB (Spain) con el objetivo de identificar diferencias y regularidades e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 41 publications
0
10
0
6
Order By: Relevance
“…Four studies (Larson et al, 2007;Marrs et al, 2007;Rubinstein, 2005;Vedel et al 2015) included gender as an independent variable in factorial designs, and Clariana (2013) performed t-tests to compare males and females in terms of the Big Five personality traits. Clariana (2013), Larson et al (2007, Rubinstein (2005), and Vedel et al (2015) found significant gender differences in Agreeableness; females scored significantly higher than males (p < .01). Clariana 2013, Rubinstein (2005), and Vedel et al (2015) also found significant gender differences in Conscientiousness; again, females scored significantly higher than males (p < .05).…”
Section: Gender Differencesmentioning
confidence: 88%
See 1 more Smart Citation
“…Four studies (Larson et al, 2007;Marrs et al, 2007;Rubinstein, 2005;Vedel et al 2015) included gender as an independent variable in factorial designs, and Clariana (2013) performed t-tests to compare males and females in terms of the Big Five personality traits. Clariana (2013), Larson et al (2007, Rubinstein (2005), and Vedel et al (2015) found significant gender differences in Agreeableness; females scored significantly higher than males (p < .01). Clariana 2013, Rubinstein (2005), and Vedel et al (2015) also found significant gender differences in Conscientiousness; again, females scored significantly higher than males (p < .05).…”
Section: Gender Differencesmentioning
confidence: 88%
“…Samples were large in most studies and ranged from 168 to 3,295 students, and mean age in the studies ranged from 18.2 to 25.8 years. In three studies mean age was not reported, though (Clariana, 2013;Marrs, Barb, & Ruggiero, 2007;Pringle, DuBose, & Yankey, 2010). There were generally more females than males in the study samples, although this varied depending on the specific majors being compared.…”
Section: Study Designs and Samplesmentioning
confidence: 99%
“…Also, previous and recent studies have informed of evidence in relation to the behavioral consequences of task postponement - procrastination - as a negative or avoidance conduct in the academic environment (Clariana, 2013; Sommer, 2013; Balkis and Duru, 2017), and of the positive experience -flourishing- on health (Pattinson and Edgar, 2016). However, despite the previous evidence, the relation between these three psychological constructs has not been established with high precision.…”
Section: Introductionmentioning
confidence: 99%
“…De-regulation (DR), or low in self-regulation , may be defined as the degree of negative proactivity , that is, of active and inadequate management to regulate one's behavior. This de-regulation avoids the effort involved in proactive self-regulation of health, and of the procrastination (Clariana, 2013; Balkis and Duru, 2017). In a previous research report, examples of this theoretical formulation were presented (de la Fuente, 2017, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Present hedonist orientation has been positively related in education, to another temporal variables such procrastination, which is studied in relation to academic outcomes among HE students samples (e.g. Clariana, 2013). Furthermore, future oriented individuals are characterized by delay of gratification, as results of the desire to achieve specific long-term goals.…”
Section: Introductionmentioning
confidence: 99%